Innovating for today while innovating for tomorrow: a test of innovation ambidexterity theory in a leading technology company - Fernholz, Olga (2018)
The theory of ambidextrous organisation in management and organisational studies latches onto the idea of simultaneous and equally high degrees of incremental innovation based on prior knowledge (exploitation) and discontinuous innovation based on experimentation and new knowledge (exploration). It claims that any organisation should be ambidextrous to succeed long term. This thesis research puts ambidexterity theory to test. Using the logic of falsification, I conduct an exploratory case study of the semiconductor IP designing company ARM to tests whether the central claims of ambidexterity apply in the empirical context of this successful technological company. The ARM is a leading-edge innovator and a successful company by any common sense criteria. I find that ARM used and banned the ambidexterity rationale because its underlying assumptions misrepresent the interactions between ARM and its Partners in the process of innovation across its vast Ecosystem. I find that ambidexterity assumptions break down in the context of the Ecosystem. Ambidexterity theory displays some serious limitations when applied to the company’s innovation in System-on-a-Chip technology that powers ubiquitous computing and assembles an Ecosystem of Partners. The revealed limitations of ambidexterity thinking demand to reconsider the claim of ambidexterity’s universal value and to reassess the fitness of ambidexterity assumptions for explaining innovation in the technology of the future.